COMPOSITION AND MICROSTRUCTURE OF MgAl2O4–W COMPOSITE OBTAINED BY ALUMINOTHERMIC REACTION UNDER COKE PROTECTION - Han Bingqiang; Ao Jinqing; Ke Changming; Li Nan (Ceramics-Silikáty, 2011)
MgAl2O4–W composite was synthesized by aluminothermic reducing method using Al, WO3, MgO and corundum as raw materials under coke protection. The effects of temperature, content of corundum on the synthesis of MgAl2O4–W composite and lattice parameter of spinel has been discussed. The differential scanning calorimetry (DSC) and thermogravimetric (TG) analysis indicated that spinel began to form at 1058.2°C without corundum and shifted to 1120.7°C with 0.8 mol of corundum. The XRD analysis confirmed that spinel and tungsten are the main phases under coke protection. Alumina rich spinel with a high solubility of alumina was easily formed because of the high exothermic heats. The solubility limit of Al2O3 in spinel is reached when corundum content is 2.1 mol. Furthermore, the calculated lattice parameter of spinel increases with the increment of added corundum content and rising of temperature. Microstructural observation indicates that cubic tungsten located at grain boundaries of well crystallized spinel. Residual WO3 has needle like morphology.